What Determines Price-to-Earnings Ratios: An Empirical Evidence from Banking Sector of Pakistan - SAFDAR HUSSAIN TAHIR; MUHAMMAD RIZWAN ULLAH; DR. SAID SHAH (Journal of Business & Tourism, 2021)
It is of greater importance to understand the factors influencing P/E ratio for the fund managers, decision makers, market analysts and individual investors. Variability in shares prices and investment opportunities in Pakistani listed banking firms motivate to examine the determinants of P/E ratio using time-series as well as panel data analysis for the period of 2007 to 2014. The findings of panel data indicate significant variation in P/E ratio due to MktRtrn, VMP and SIZE. DP ratio is found to be the most influential determinant of P/E ratio indicating the willingness of investors to invest more funds in those banking firms paying greater dividends. Empirical outcomes of time-series analysis for banking industry represent that DP ratio is the super most imperative determinant of P/E ratio. Findings also indicate that P/E ratio vary across years and influence the investor’s investment decision. The findings of the study facilitate the decision makers by investigating the most significant determinant of P/E ratio of banking firms in order to attract attention of investors and increase their confidence to choose these firms in their portfolios.